THE ROLE OF MALAYSIAN AND INDONESIAN ULAMA IN HADITH STUDIES: Muhammad Idris al-Marbawi and T.M. Hasbi Ash Shiddieqy - Ramli Abdul Wahid; A. Irwan Santeri Doll Kawaid (UIN Sumatera Utara, 2019)
Abstrak: Studi ini mengkaji perbandingan peran Muhammad Idris al-Marbawi dari Malaysia dan Muhammad Hasbi Ash Shiddieqy dari Indonesia dalam bidang hadis. Kedua ulama dinilai telah memberikan kontribusi bagi studi hadis di dua negara. Studi ini merupakan studi kepustakaan. Data penelitian diperoleh melalui kegiatan studi dokumen. Karya-karya kedua ulama dijadikan sebagai sumber primer dan hasil penelitian para ahli tentang kedua ulama dijadikan sebagai sumber sekunder. Berdasarkan analisis terhadap data penelitian, studi ini menemukan bahwa kedua ulama telah menulis dalam bidang hadis. Selain bidang hadis, kedua ulama yang hidup dalam periode yang sama tetapi berasal dari negara yang berbeda ini juga menulis dalam bidang ilmu keislaman lainnya terutama tafsir, fikih. Bedanya, al-Marbawi mengembangkan kajian tasawuf, sedangkan Ash Shiddieqy tidak pernah menulis dalam disiplin tersebut. Abstract: Peran Ulama Malaysia dan Indonesia dalam bidang Hadis: Muhammad Idris al-Marbawi dan T.M. Hasbi Ash Shiddieqy. This study compares the roles of Muhammad Idris al-Marbawi from Malaysia and Muhammad Hasbi Ash Shiddieqy from Indonesia in the field of hadith. Both scholars were considered to have contributed to the study of hadith in respective countries. This study is a library research, the data of which was obtained through documentary study. The works of the two scholars were used as primary sources and the the previous researches of expert on the two scholars were used as secondary sources. This study found that both scholars had involved in hadith studies and left a number of important works in the field. The authors also found that the two scholars who lived in the same period but in a different country also wrote in other Islamic fields, especially Qur’anic exegesis and Islamic law, in addition to hadith. The difference is that al-Marbawi developed the study of sufism, while Ash Shiddieqy had never wrote in this field. Kata Kunci: Hadis, ulama, Malaysia, Indonesia, al-Marbawi, Ash Shiddieqy